Effect of Oxide Nanoparticles on Thermal and Mechanical Properties of Electrospun Separators for Lithium-Ion Batteries. (31st October 2012) - Zaccaria, Marco; Gualandi, Chiara; Fabiani, Davide; Focarete, Maria Letizia; Croce, Fausto
Abstract : This study reports the fabrication and characterization of poly(ethylene oxide) (PEO) and poly(vinylidenefluoride-co-chlorotrifluoroethylene) (PVDF-CTFE) nanofibrous separators for lithium-ion batteries loaded with different amounts of fumed-silica and tin oxide nanoparticles. Membrane morphological characterization (SEM, TEM) showed the presence of good-quality nanofibres containing nanoparticles. Thermal degradation and membrane mechanical properties were also investigated, and a remarkable effect of nanoparticle addition on membrane mechanical properties was found. In particular, PEO membranes were strengthened by the addition of metal oxide, whereas PVDF-CTFE membranes acquired ductility.